Macrophage autophagy in macrophage polarization, chronic inflammation and organ fibrosis - Wen, Jun-Hao; Li, Dong-Yi; Liang, Shan; Yang, Chen; Tang, Ji-Xin; Liu, Hua-Feng (Frontiers in Immunology, 2022)
As the essential regulators of organ fibrosis, macrophages undergo marked phenotypic and functional changes after organ injury. These changes of macrophage phenotype and function can result in maladaptive repair, causing the chronic inflammation and the development of pathological fibrosis. Autophagy, a high conserved lysosomal degradation pathway, is one of the major players to maintain the homeostasis of macrophage through clearing protein aggregates, damaged organelles and invading pathogens. Emerging evidences has shown that macrophage autophagy plays an essential role in the macrophage polarization, chronic inflammation and organ fibrosis. Because of the highly heterogeneity of macrophages in different organs, different macrophage types may play different roles in organ fibrosis. Here, we review the current understanding of the function of macrophage autophagy in macrophage polarization, chronic inflammation and organ fibrosis in different organs, highlight the potential role of macrophage autophagy in the treatment of fibrosis. Finally, the important unresolved issues in this field are briefly discussed. The better understanding of the mechanisms that macrophage autophagy in macrophage polarization, chronic inflammation and organ fibrosis may contribute to develop novel therapies for chronic inflammatory diseases and organ fibrosis.